IMPLEMENTATION OF THE ARGUMENT-DRIVEN INQUIRY (ADI) LEARNING MODEL TO IMPROVE LEARNING OUTCOMES AND COMMUNICATION SKILLS OF EIGHT GRADE STUDENTS OF SMP NEGERI 24 MAKASSAR - Raodatuljanna, Maghfira Nur; Hasanuddin, Hasanuddin; Saenab, Sitti (Jurnal IPA Terpadu, 2024)
Abstract:This study aims to determine: 1) The level of learning outcomes and communication skills of students before and after the implementation of ADI; 2) Improvement in learning outcomes and communication skills of students after the implementation of ADI; 3) significant improvement in learning outcomes and communication skills of students. This type of research is Pre-Experimental Design with a one group pretest-posttest research design. The population is 315 students of class VIII SMPN 24 Makassar. A sample of 27 students using purposive sampling technique. The research instruments are in the form of learning outcome tests and communication skills questionnaires which are analyzed with descriptive and inferential statistics. The results of the study show; 1) The level of learning outcomes before the implementation of ADI is in the low category with a score of 6.04 and after the implementation of ADI is in the high category with a score of 14.07. The level of communication skills before the implementation of ADI is in the moderate category with a score of 26.00, while after the implementation it is in the very high category with a score of 48.89; 2) The increase in students' science learning outcomes after the implementation of ADI is in the moderate category with an N-Gain score of 0.59. The improvement of communication skills is in the moderate category with an N-Gain score of 0.67. 3) there is a significant increase in learning outcomes with t-count = 11.50> t-table = 1.706. This means that H0 is rejected and H1 is accepted and in communication skills with a p-value of 0.001 <0.05. means that H0 is rejected and H1 is accepted.